ANALISA BRANDING MELALUI KONTEN VISUAL PADA INSTAGRAM SEBAGAI USAHA MEMPERKENALKAN BUDAYA MINUM WINE DI BALI - Hanindharputri, Made Arini; Irhandi, I Gusti Ngurah Gede Gitayogi; Budiarta, I Gede Bayu (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2020)
The tradition of drinking alcohol has been known for generations, not only being a part of religious activities or traditional celebrations, but also becoming a tradition in familiarizing people with each other from various circles. Bali as a tourist destination that has a tradition of drinking liquor became the right destination for wine companies to operate and produce wine in Bali. This will be very interesting for foreign tourists visiting Bali to be able to taste wine with different tastes and be able to introduce the tradition of drinking wine to the Balinese people through branding on Instagram media. In this writing, the authors analyse the visual content strategy of several wine companies operating in Bali, to be able to know the extent to which the wine company introduced the culture of drinking wine to foreign tourists and the Balinese themselves. Keywords: Branding, Instagram Visual Content, Wine Company, Bali